Oral manifestations of Crohn's disease - Marković Ljiljana; Ljušković Bešir (Serbian Medical Society - Dental Section, Belgrade, 2004)
Crohn's disease is a chronic granulomatous inflammatory bowel disease of unknown cause. Segments of the whole gastrointestinal tract may be involved, including the oral cavity. The most common oral manifestations of Crohn's disease are edema, ulcerative and hyperplastic lesions. They appear most commonly on the lips, gingival tissue and buccal mucosa. Oral manifestations of Crohn's disease may precede intestinal symptoms. Recognition of these oral manifestations may lead to quicker diagnosis and earlier adequate treatment. If Crohn's disease is diagnosed, the dentist must make a detailed oral cavity examination and implement treatment of the existing oral lesions. Also, the dentist must provide prevention against caries and periodontal disease in these patients. Considering the frequency of oral manifestations of Crohn's disease, cooperation between gastroenterologist and dentist is very important.